حقوق المرأة العاملة: دراسة مقارنة بين الشريعة الإسلامية والقوانين الوضعية - العقايلـة, زيـد محمـود (revue mofakir; No 08 (2012): مجلة "المفكــــــر, 2018)
The legislator in the Hashemite Kingdom of Jordan and the United Arab Emirates has enacted a special law in order to organize the relationship between employees and employers in away that it achieves the benefit of both parties, pushes the development process forward, and increase the productivity, through encountering the humanitarian and social needs which may arise during work and coping with the successive developments at the economic and social levels. Hence, protection of a worker, particularly woman, providing her with the legal securities relating to her humanitarian, social and health needs, and enabling her to make conciliation between her work and her family duties will positively affect her productivity, and as a result achieve the interest of the employer. In addition, it enhances her sense of tranquility which participates in the preservation of the social security and peace. This article has discussed the rights of the working woman in the Jordanian and the UAE labour law during her work and it has put forward many related suggestions and recommendations. ملخص : لقد قام المشرع في كل من المملكة الأردنية الهاشمية ودولة الإمارات العربية المتحدة بسن قانون خاص بالعمل لكي ينظم العلاقة بين العمال وأرباب العمل على نحوٍ يحقق مصلحة الطرفين ويدفع مسيرة التنمية ويزيد الإنتاج وذلك من خلال مواجهة الحاجات الإنسانية والاجتماعية التي قد تظهر في نطاق العمل ومواكبة التطورات المتلاحقة على الصعيدين الاقتصادي والاجتماعي . فحماية العامل - وخاصةً المرأة - وتوفير الأحكام القانونية الخاصة بحاجاتها الإنسانية والاجتماعية والصحية وتمكينها من التوفيق بين عملها وبين واجباتها الأسرية من شأنه أن ينعكس إيجاباً على إنتاجيتها ويحقق مصلحة رب العمل، كما أنه يعزز الشعور بالطمأنينة مما يساهم في الحفاظ على الأمن والسلام الاجتماعيين . ناقش هذا البحث حقوق المرأة العاملة في الشريعة الإسلامية وقانوني العمل الأردني والإماراتي أثناء ممارستها للعمل وخَلُص إلى وضع عدة اقتراحات وتوصيات متعلقة بهذا الشأن .